Identification the influence of increased pore water pressure and vertical deformation under the influence of the liquefaction - Munawir, As’ad; Zaika, Yulvi; Suryo, Eko Andi; Charisma, Nuril; Alihudien, Arief (Eastern-European Journal of Enterprise Technologies, 2025)
This study examines how increase in pore water pressure weakens the sand foundation, triggers liquefaction and lateral shift. This is related to the interaction of pressure, density, depth, and load through experiments and simulations to increase the foundation design. Numerical analysis using UBC3D-PLM 3D plaxis, while experimental tests are carried out with a 2.2 kW electric motor-powered table. Experiment uses an acrylic ground box 0.5×1×1.5 m3 which is strengthened by steel. The foundation model is in the form of a 2×2 pole group with four pillars and pile caps. The results of the study showed an increase in pore water pressure due to vertical and earthquake loads could trigger liquefaction and vertical deformation. Numerical analysis shows a surge in pressure in 20 seconds, in the case exceeding the 7.0 ratio, shows full liquefaction. The vibrating table experiment (relative density of 10 %) shows RU values close to 1, confirming the potential for liquefaction. Both experiments and simulations indicate rapid initial deformation before stabilization. Pore water pressure jumped to the critical level before stable, indicating the potential for full liquefaction. Non-linear vertical deformation confirms significant soil changes below the dynamic load. This study identifies the limit of the pressure ratio for partial and full liquefaction and soil response to vertical and seismic loads. The combination of numerical and experimental data allows the analysis of vertical deformation of foundation stability. This finding supports the design of earthquake resistant foundations and geotechnical risk assessment, although its application must consider soil conditions and limitations of numeric models, so it is necessary to be further calibration for prediction accuracy